Historia edukacji osób autystycznych w Polsce na tle zmian zachodzących wokół zaburzenia ze spektrum autyzmu - Buława-Halasz , Joanna (Biuletyn Historii Wychowania, 2023)
The text is an attempt to organize the knowledge about the history of education of autistic persons in Poland, and to present this process against the background of changes taking place around the autism spectrum disorder (ASD). The three most important events in this area are: the new conceptualization of this disorder in the International Classification of Diseases, 11th Revision, the implementation to the standard of education of teachersmajoring in the education and therapy of persons with the autism spectrum disorder, and the demise of Professor Tadeusz Gałkowski, a researcher and activist who was the first to recognise this disorder in Poland.